Les communs comme infrastructure institutionnelle de l’économie marchande - Gilles Allaire (Revue de la Régulation)
This paper concerns the immaterial common resources systems which form the cultural environment of production, trade and administration activities. It suggests that the commons make up an infrastructure of modern market economies. Based on Elinor Ostrom works, it proposes three main theses. Not only the differences in the origin and the functioning of immaterial and physical commons do not suppress their similar nature, for both are institutional structures which regulate the access to and the managing of common resources according to a common aim and not without conflicts, but in addition common resources systems generally associate the two types of commons. Commons are not a past legacy. On the contrary, vast and complex common resources systems are constructions developing in the course of market systems development. In a given context, the relations between common resources systems, and between such systems, markets, and law, lead to uncertain dynamics of these systems, the value of which is thus intangible, depending on conditions in the future. In their development or regressive dynamics, common resources are affected by the ways there are used, and valorized, and there are threaten by bad uses. But their future is also depending on technological, social, and market dynamics related to the activities of users. This perspective which put in the forefront the relations and interdependencies between commons and markets offers analytical tools of the institutional diversity and complexity of economies.